Une Analyse Structurale de Trois Pièces d'Eugène Ionesco - Leousis, T. (My University, 1974)
The purpose of this paper will be to make a careful analysis of the various structural techniques which Eugène Ionesco uses in the three long plays: Amédée ou Comment S'en Débarrasser?, Rhinocéros, and Jeux de Massacre. Great attention will-be paid by the author to the creation of scenic atmosphere and to the originality of Ionesco's use of the elements of suspense and tempo. The author will also discuss in depth the importance of certain aspects of the stage decorations and the rôles of the most unusual jeux de scène of the three plays. In the Conclusion, there will be a final discussion of the basic similarities and differences between these plays.
Keywords: Romance Languages; Other Languages, Societies, and Cultures; Other Languages, Societies, and Cultures